Impact of treated sewage effluent on the microbiology of a small brook using flow cytometry as a diagnostic tool - Harry, Ibiye S. K.; Ameh, Ekwu Mark; Coulon, Frederic; Nocker, Andreas (Springer, 2016)
Flow cytometry was applied to assess the microbiological impact of treated sewage effluent discharge into a small brook carrying surface runoff water. Increases in dissolved organic carbon and soluble reactive phosphorous were accompanied by increases in counts of intact bacteria by up to eightfold. Effluent ingress furthermore resulted in a pronounced shift of bacterial clusters. Whereas brook water upstream of the discharge point was characterised by a bacterial cluster with low nucleic acid (LNA) content, downstream water showed a shift to bacteria with high nucleic acid (HNA) content. Changes in the LNA/HNA ratio were largely maintained along the course of the brook. Results suggest that the LNA/HNA ratio can under certain conditions serve as an indicator of anthropogenic nutrient impact. Measuring impact on this low trophic level might be more sensitive and straightforward than measuring macroindicators. More evidence will however be required to assess the usefulness of LNA/HNA measurements to assess the ecological nutrient status of natural waters and the impact of nutrient pollution.
Keywords: Microbiological water quality; Water ecology; Wastewater effluent; Flow cytometry; High nucleic acid bacteria; Low nucleic acid bateria; Phosphate